A Study on the Implementation of Songs in Teaching Vocabulary - Riska Juliana; Konder Manurung (JURNAL BANUA OGE TADULAKO, 2022)
The objectives of this study are to analyze, describe, and explain the implementation of songs in EFL classes of vocabulary mastery by previous researchers. This study was conducted descriptively through Library Research Method. The secondary sources analyzed, described, and explained in this study were taken from the scientific writing published from 2010 to 2019 from kindergarten to university levels. The sources consisted of ten previous studies, eight skripsis and two articles. The results of descriptive data analysis show that the implementation of songs by previous researchers was done through integrating vocabulary learning with the song lyrics by using some procedures tha (1) explain the words/topic (noun, verb, or adjective); (2) provide song lyrics to the EFL students (as groups or individuals); (3) play songs for at least two times; (4) asks the EFL students to identify the vocabulary or expressions they find in the song lyrics provided; (5) discusses the songs he/she plays with the EFL students and asks the EFL students about their opinion regarding songs they listen to; (6) asks one EFL student to write the answer on the whiteboard; (7) If the answer is correct, the teacher will give feedback to the EFL students by complementing those who have correct answers and; (8) If the answer is incorrect, the teacher will explain the correct answer to the EFL students and its reasons. All the secondary data sources imply that the implementation of songs provides clear examples for the EFL students and reduces their stress during their vocabulary mastery experience. In conclusion, the implementation of songs is appropriate for the EFL students from kindergarten to high school levels. Then, the implications of implementing songs are to make the EFL students more stimulated to learn vocabulary in EFL classes and songs stimulate the EFL students to reduce their stress level during the class